2019
DOI: 10.3808/jeil.201900004
|View full text |Cite
|
Sign up to set email alerts
|

Response of Surface Water Quality in Urban and Non-urban Areas to Heavy Rainfall: Implications for the Impacts of Climate Change

Abstract: Frequency and intensity of floods and droughts are increased across the world due to global climate change. However, the responses of water quality in urban and non-urban areas to extreme weather events are not well understood. The heavy and extensive precipitation during the summer of 2011 and 2012 caused two severe floods in Beijing of China. This work evaluated the impacts of these two floods on the water quality of 10 urban lakes, 3 non-urban reservoirs, and 8 non-urban rivers through comparing the pre-flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…The associated effects on the environment include noise and air pollution, land occupancy, and traffic accidents. Urban dispersion uses up land that would otherwise be available for ecological uses, while the excessive energy consumption leads to air pollution, exhaustion of non-renewable energy, and gas emissions, which ultimately contribute to climate change (Anderson et al, 1996;Wu and Xia, 2019;Chen et al, 2020;Liu et al, 2020). Ewing and Rong (2008) conducted a study investigating the relationship between the choice of housing type and urban form, and found that multifamily housing is seven time less popular in dispersed areas than in compact areas.…”
Section: Dispersed Citymentioning
confidence: 99%
“…The associated effects on the environment include noise and air pollution, land occupancy, and traffic accidents. Urban dispersion uses up land that would otherwise be available for ecological uses, while the excessive energy consumption leads to air pollution, exhaustion of non-renewable energy, and gas emissions, which ultimately contribute to climate change (Anderson et al, 1996;Wu and Xia, 2019;Chen et al, 2020;Liu et al, 2020). Ewing and Rong (2008) conducted a study investigating the relationship between the choice of housing type and urban form, and found that multifamily housing is seven time less popular in dispersed areas than in compact areas.…”
Section: Dispersed Citymentioning
confidence: 99%